DYNAMICS OF ACADEMIC STRESS IN MADRASAH IBTIDAIYAH STUDENTS: A PHENOMENOLOGICAL STUDY - Febyana Damayanti; Ghozali Rusyid Affandi (P3I UMSurabaya, 2024)
This study examines academic stress in Madrasah Ibtidaiyah students aged 10-12 years, a critical stage in children's psychological and academic development. The research employed a phenomenological approach to understand the experiences of two students dealing with a heavy academic workload. Data were collected through interviews and observations, focusing on emotional, cognitive, physiological, and behavioral aspects. The findings revealed that academic stress was caused by factors such as a large volume of tasks, pressure to perform, and lack of support and effective time management. This stress negatively impacted students' mental health, leading to anxiety, mood swings, sleep disturbances, and other physical symptoms. The study underscores the need for emotional support from teachers and parents, as well as the importance of balancing academic demands with recreational activities to promote psychological well-being.